FACTORS INFLUENCING DRUGS AND SUBSTANCE ABUSE AMONG PUBLIC SECONDARY SCHOOL STUDENTS IN KIAMBU COUNTY, KENYA - Kiambi, Muriithi Joel (International Journal of Psychology, 2018)
Purpose: The main objective of this research was to assess the factors influencing drugs and substance abuse among public secondary school students in Kiambu County Kenya. Methodology: Mixed methodology was used to gather both qualitative and quantitative data. A descriptive survey study design was used to assess the factors influencing public secondary school students. The target population comprised of form three students and teachers from public secondary schools. The sample size was 140 respondents. Simple random sampling and purposive sampling techniques were used in respondent selection. The study instrument was structured questionnaires. After data collection, quantitative data was cleaned, coding and then entered into SPSS software version 21.0. Quantitative data was analyzed and presented in the form of frequencies and percentages, in Tables and Figures using SPSS software. Further, inferential statistics was used to test for relationship at 95% confidence level. All logical and ethical issues pertaining to research were also adhered to by the researcher throughout the process of writing this study. Results: The results of the study revealed that drugs and substance abuse was generally prevalent among public secondary school students in Kiambu County. However, the male learners in this study were found to be mostly affected by drugs and substance abuse compared to the female students in similar schools. The study also established that peer pressure influenced drugs and substance abuse among public secondary school students to a high extent. According to the results, alcohol consumption by students is most influenced by peer pressure followed by cigarette smoking, bhang smoking, Khat chewing and cocaine consumption in Kiambu County. Lastly, the study also established that being in a mixed school greatly influenced drugs and substance abuse among public secondary school learners, followed by belonging to a single gender school whereas being in a boarding school influenced drugs and substance abuse among public secondary school learners the least. Unique Contribution to Theory, Practice and Policy: The study recommends that urgent attention need to be given to mixed secondary schools as drugs and substance abuse is very prevalent in these schools. All education stakeholders in Kiambu County ought to work together in order to eliminate drug and substance abuse among the students as this is an endeavor that cannot be achieved by a single party alone.